Vídeos do impresso: formatos e rotinas produtivas no Diário de Pernambuco e Jornal do Commercio - Jacinto, Gil Aciolly Dantas (2019)
This research aims to investigate the audiovisual production carried out by newspapers. Traditionally, these media have consolidated their journalistic practices based on codes such as writing and still image. Currently, they are using moving images to contextualize narratives driven by convergence media trends. We use Content Analysis to identify the main features and formats employed by two local newspapers - Diario de Pernambuco and Jornal do Commercio - in different platforms. Our hypothesis is that organizational culture, productive routines and social media platforms, in the context of convergent journalism, imprint marks on language, reconfiguring formats, indicating new ways of journalistic expression and a resignification of news with audiovisual content. To support this investigation, we also conducted In-Depth Interviews with professionals from these media. The theoretical support is anchored in the concepts of convergence, multimediality, multiplatform, narratives, genre and formats. Our findings shows how social media platforms and print professional cultural influence audiovisual production. Also, we identified that videos produced by local newspapers can play different roles depending on the platform on which they are distributed. Finally, we found an increasing dependance of newspapers on social media platforms to which audiovisual production is increasingly directed.